PENGARUH DRUMUS OIL SEBAGAI MEDIA PENDINGIN TERHADAP PENINGKATAN KEKERASAN DAN TRANFORMASI FASA PADA PROSES PENGERASAN BAJA AMUTIT - Karmin, Karmin; Yunus, Moch; Ginting, Muchtar (Politeknik Negeri Sriwijaya, Indonesia, 2014)
Engineering process technology is basically an effort to optimize the use of natural resources effectively and efficiently in order to provide maximum benefit for the benefit of human life. Amutit steel is one of the low alloy steel which is identical to AISI O1 standard. This steel hardness can be increased through a heat treatment process that allows used for industrial purposes as cold work tool steels as well as other purposes. In this research the process of hardening, the steel is heated to a temperature of 8200 C and then cooled rapidly using a coolant emulsion (dromus oil with water). To reduce brittle properties and improve the ductility, the steel is then heated again at a temperature of 4000 C and held for one hour and cooled slowly in the furnace. The results amutit hardening of steel using a coolant with a mixture ratio variations dromus oil with water, after tempering highest hardness is 590 HV, obtained using dromus oil emulsion with water 1:30 ratio while using oil as quenching media produced 544 HV hardness.